Analisis Hubungan Karakter Rasa Ingin Tahu dengan Hasil Belajar Peserta Didik Kelas V SD - Silvia, Nina; Ilyani Ropida; Silvia, Ninda (Journal of Basic Education Research, 2022)
Research Objectives: This study aims to determine the relationship between the character of curiosity and the learning outcomes of fifth grade students. Research Methods: This research is a type of quantitative research, the method used is correlation which aims to connect. The sample in this study was 28 students of class V SD Negeri 66/IV Jambi City, the sampling technique was total sampling. The data collection instruments used were questionnaires and multiple choice questions. Data analysis uses descriptive statistics, to analyze the data by describing or describing the data that has been collected. And the correlation test to test the proposed hypothesis. Main Findings: The results obtained indicate that the social character possessed by students is included in the good category, seen from the character of curiosity has a relationship with learning outcomes, strengthened by the correlation results obtained by 0.045. Therefore, it is important for teachers or educators to improve the character of students' curiosity so that student learning outcomes also increase. Novelty This Resarch: The novelty of this research is to examine the relationship between the character of curiosity and the learning outcomes of fifth grade students.